IMPROVING THE EFFICIENCY OF OUR COUNTRY'S COMMERCIAL BANKS' ASSETS ISSUES - Kholmuradov Musurmon Avlakulovich (Innovate Conferences, 2025)
Ensuring the quality of asset portfolios of commercial banks, the need to ensure their financial stability and liquidity is considered one of the current issues. In this scientific article, an attempt was made to develop a scientific proposal and practical recommendations on ways to increase the efficiency of the assets of commercial banks.
Keywords: bank, bank assets, risk, national economy, bank portfolio, asset quality, banking system, loan portfolio, investment